Implementasi Metode Mengajar Tuhan Yesus Kristus Berdasarkan Injil Markus Di Kalangan Hamba Tuhan GUPDI Wilayah IX Kabupaten Sekadau - Sinardi, Sinardi; Suparti, Hana; Sugiyarto, Kristian Handoyo (Jurnal Teologi (JUTEOLOG), 2024)
The testaments of the kingdom of heaven and Jesus Christ must be delivered to all people around the world because the Lord Jesus Christ came to the world to save people from demise. The right teaching method can have a great impact on servants of God in delivering and teaching the testament of the kingdom of heaven. These methods can help God's people resolve their problems by learning and teaching God's words. If we look at the Gospel of Mark, we see that the Lord Jesus Christ taught in a very compelling way, which attracted many people to listen to His teaching. As educators, they should emulate the way the Lord Jesus taught. This must be done so that their lessons can have a significant impact on the people they teach. The Bible provides a wealth of information on the teachings taught by the Lord Jesus Christ. The teachings taught by the Lord Jesus Christ always fulfill the needs of His disciples. Scholarly research on the Gospel of Mark found various methods of Jesus' teaching, including discussions, parables, questions and answers, props, and lectures. Every educator, teacher, lecturer, and servant of God of the Pentecostal Messenger Church in Indonesia Region IX Sekadau Regency can use all five of Jesus' teaching methods in the education process, especially in churches and theological schools. Jesus, as a great teacher, has demonstrated an innovative way to teach. He used varied learning methods. So that the growing of faith can be achieved optimally, Christian education in the Church can use Jesus' teaching methods in a way that suits the congregation's circumstances.